The Dark Triad and dispositional aggression. (November 2015) - Jones, Daniel N.; Neria, Adon L.
Abstract: Previous research has demonstrated that people who are callous are more likely to be interpersonally aggressive. The present study extends this finding to research on the " Dark Triad " traits (Machiavellianism, narcissism, and psychopathy), which all share a common core of callousness and manipulation. Using crowd-sourcing and student samples, we examined the relationship between the Dark Triad traits with different facets of dispositional aggression. Results indicated that a common Dark Triad factor (i.e., callousness and manipulation) predicted a common aggression factor. However, the individual Dark Triad traits uniquely predicted different facets of aggression. Psychopathy positively predicted physical aggression, narcissism negatively predicted hostility, and Machiavellianism positively predicted hostility. Taken together, the findings shed light on the unique elements of the Dark Triad and their ability to predict unique forms of dispositional aggression. Highlights: The Dark Triad should differ in which aspects of aggression to which they should be related. The common factor of the Dark Triad predicted a common factor of aggression. Psychopathy predicted additional positive variance in physical aggression. Machiavellianism was positively related to hostility and narcissism was negative. Manipulation and entitlement facets were unrelated to unique aspects of aggression.